CONTRIBUTION OF FINANCE DIVISION INTERNSHIP STUDENTS IN SUPPORTING THE TBC ELIMINATION PROGRAM THROUGH THE MSIB INTERNSHIP PROGRAM AT THE MENTARI MERAKI ASA FOUNDATION - Natalia Sitorus; Herlina Xie; Akbar Hidayat; Karlina Simomora (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium Tuberculosis and is one of the most significant public health problems in Indonesia. This service was carried out to see what roles can be played by financial division interns in order to help in preventing TB in Indonesia, especially in North Sumatra.This service uses a descriptive qualitative approach using data collection instruments of participatory observation, interviews, documentation and document analysis. The subject of this service is a program at the Mentari Meraki Asa Foundation. The results of this service resulted in several direct involvement initiatives in the process and also several new systems created by service participants. Some of these systems are ISAK 35-based Accounting Information Systems, Foundation Financial Standard Operating Procedures (SOP), and Income Tax (PPh) 21 calculation templates.